An Investigation on the Relationship between Personality Traits and Grit Levels among Pre-Service English Language Teachers - Yram Art Morrok (International Journal on Integrated Education, 2022)
Grit has been a renowned construct in the fields of education (Duckworth & Quinn, 2009) and profession (Baum & Locke, 2004). Similarly, personality traits have also been long acknowledged by different researchers as a determiner of one’s likelihood to succeed too. It is depicted as an internal characteristic noted for its relative stability, consistency, and longevity (APA). As they are equal key determiners, it is intriguing to know whether there is a relationship between these two. The current study aims to realize this among pre-service English language teachers as respondents. Big Five Personality Traits Scale and Short-Grit Scale were utilized in gathering the necessary data for such, while a Personal Information Section was provided to identify the demographics of the respondents. Sequentially, it was revealed that there is indeed a statistically significant relationship between the personality traits of the respondents, such as conscientiousness and openness, and their grit levels.